Energy Efficiency as a Factor of Sustainable Development in Kazakhstan - Soltangazinov, Aibek; Smagulova, Zubirash; Amirova, Maral; Kashuk, Lyudmila; Karimbergenova, Madina; Kadyrova, Akmaral; Zhaltyrova, Olga (International Journal of Energy Economics and Policy, 2019)
The principles of sustainable development and the green economy are aimed at improving energy efficiency. Kazakhstan’s joining the international environmental movement testifies to the country’s desire to reduce the energy intensity of the economy and to carry out practical actions aimed at sustainable development. This is confirmed by target indicators in the field of energy efficiency, which are reflected in the documents of the State Planning System of the Republic of Kazakhstan and are aimed at increasing energy security, labor productivity, the rational use of budget funds, as well as improving the health and welfare of citizens. The current energy balance of Kazakhstan is dominated by coal, used primarily by thermal power plants to generate electricity. Therefore, GDP’s high energy intensity is indicative of irrational energy consumption, which is accompanied by an increase in environmental pollution. This paper gives a review of some aspects of the energy saving sphere and the international energy saving experience, as well as analyzes the current situation with regard to the implementation of energy efficiency policies in Kazakhstan. The study shows that the domestic economy has a significant energy saving potential in key sectors of the economy, identifies energy efficiency problems, and proposes solutions to them. Keywords: energy efficiency, decarbonization, energy intensity, energy-saving technologies, green economy, sustainable development. JEL Classification: Q4 DOI: https://doi.org/10.32479/ijeep.8618